2005
DOI: 10.1211/0022357055641
|View full text |Cite
|
Sign up to set email alerts
|

Medication reviews provided by general medical practitioners (GPs) and nurses: an evaluation of their quality

Abstract: Objective To train general medical practitioners (GPs) and nurses in providing medication review services in the primary care setting and to evaluate the reviews provided. Setting One medical practice in Scotland with five whole‐time equivalent (WTE) GP partners, two practice nurses and six community‐based nurses. Method Training for GPs was provided as a group session plus individual supported clinic sessions. Nurse training consisted of a group session only. Patients aged over 75 were invited to attend the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…22 Furthermore, we have been unable to monitor the impact of the training on routine practice. However, we have shown that GPs are willing to accept training from practicebased pharmacists and that most viewed this as making a positive contribution to their confidence in reviewing medication.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…22 Furthermore, we have been unable to monitor the impact of the training on routine practice. However, we have shown that GPs are willing to accept training from practicebased pharmacists and that most viewed this as making a positive contribution to their confidence in reviewing medication.…”
Section: Discussionmentioning
confidence: 99%
“…27 During our training programme, changes were made in the medication of 80% of patients, although this may not be translated into routine practice following training. 22 Studies showing improved outcomes of pharmacist reviews compared with routine care suggest that both the frequency and quality of GP reviews could be improved. Little has been published on how to achieve this.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations